2021
DOI: 10.3390/ani11041103
|View full text |Cite
|
Sign up to set email alerts
|

Pork Quality of Two Lithuanian Breeds: Effects of Breed, Gender and Feeding Regimen

Abstract: The diversity of breeds is an important factor influencing carcass and meat quality traits that are also associated with other different effects. The objective of this study was to investigate the effects of breed, gender, and feeding level in the finishing phase on the carcass and meat quality of Lithuanian White and Lithuanian Indigenous Wattle pigs reared indoors. After 60 kg weight, half of the animals from both breeds were fed a restricted diet of approximately 82% of average ad libitum feeding intake, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 65 publications
2
13
0
Order By: Relevance
“…Different authors [12,17,20] found higher AI and TI indexes, but a lower h/H ratio for the meat of foals compared with those in the present study. Although horse meat showed a similar AI index and h/H ratio compared with the pork from Lithuanian pig breeds [54], it must be noted that horse meat demonstrated a considerably lower TI index.…”
Section: Fatty Acidsmentioning
confidence: 80%
“…Different authors [12,17,20] found higher AI and TI indexes, but a lower h/H ratio for the meat of foals compared with those in the present study. Although horse meat showed a similar AI index and h/H ratio compared with the pork from Lithuanian pig breeds [54], it must be noted that horse meat demonstrated a considerably lower TI index.…”
Section: Fatty Acidsmentioning
confidence: 80%
“…Pork quality is defined as a sum of many significant quality characteristics, i.e., pH, water-holding capacity, colour, tenderness, taste, and shelf life, all of which are determined by genetic and environmental factors [2][3][4][5]. However, intensive selection of livestock animals has resulted in variety negative side effects, including poorer meat quality and lower disease resistance to pigs [6]. Since 2008, to ensure high meat quality, modern pig production technologies employ markerassisted selection (MAS), which facilitates reproductive exclusion of animals burdened with the stress-sensitivity gene (RYR1) that affects the incidence of PSE meat [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some other authors have reported AI indexes [ 44 , 56 ] and similar [ 54 ] or higher TI indexes [ 42 ], but a lower h/H ratio [ 54 ]. Compared to pork [ 61 ], all lipid quality indices such as AI, TI indexes and h/H ratio of goose meat are more favourable for consumer health, however, if compared to horse meat [ 62 ], goose meat exhibits more favourable AI and h/H ratio. The peroxidizability index (PI) was higher ( p < 0.001) of IMF in the breast.…”
Section: Resultsmentioning
confidence: 99%